A review on cell damage, viability, and functionality during 3D bioprinting - Xu, He-Qi; Liu, Jia-Chen; Zhang, Zheng-Yi; Xu, Chang-Xue (Military medical research, 2022)
Three-dimensional (3D) bioprinting fabricates 3D functional tissues/organs by accurately depositing the bioink composed of the biological materials and living cells. Even though 3D bioprinting techniques have experienced significant advancement over the past decades, it remains challenging for 3D bioprinting to artificially fabricate functional tissues/organs with high post-printing cell viability and functionality since cells endure various types of stress during the bioprinting process. Generally, cell viability which is affected by several factors including the stress and the environmental factors, such as pH and temperature, is mainly determined by the magnitude and duration of the stress imposed on the cells with poorer cell viability under a higher stress and a longer duration condition. The maintenance of high cell viability especially for those vulnerable cells, such as stem cells which are more sensitive to multiple stresses, is a key initial step to ensure the functionality of the artificial tissues/organs. In addition, maintaining the pluripotency of the cells such as proliferation and differentiation abilities is also essential for the 3D-bioprinted tissues/organs to be similar to native tissues/organs. This review discusses various pathways triggering cell damage and the major factors affecting cell viability during different bioprinting processes, summarizes the studies on cell viabilities and functionalities in different bioprinting processes, and presents several potential approaches to protect cells from injuries to ensure high cell viability and functionality.